IMPLEMENTATION OF PROTOTYPE METHOD IN WEBSITE-BASED PETSHOP DIGITAL BRANDING SYSTEM - Kurniawan, Indra; Zulfa, Muhammad Choiru; Sulistyawati, Dwi Retna; Fitroh, Qorry Aina (Universitas Islam Nahdlatul Ulama Jepara, 2025)
The use of websites in today's industrial world plays a significant role. Websites are used as a medium for information, sales, and product promotion. Digital branding is an effective and superior strategy for facilitating digital communication between sellers and buyers. Through branding, companies can introduce their brands while building a positive image and reputation among consumers. This branding effort aims to foster consumer trust in the company. This research uses the prototyping method, an approach in the Software Development Life Cycle (SDLC) that focuses on developing working models. The creation of a website-based pet shop digital branding system can help shops introduce their businesses and products to buyers because it can be accessed directly from anywhere. Thus, buyers no longer need to visit the store in person to obtain information. IMPLEMENTASI METODE PROTOTYPE PADA SISTEM DIGITAL BRANDING PETSHOP BERBASIS WEBSITEThe use of websites in today's industrial world plays a significant role. Websites are used as a medium for information, sales, and product promotion. Digital branding is an effective and superior strategy for facilitating digital communication between sellers and buyers. Through branding, companies can introduce their brands while building a positive image and reputation among consumers. This branding effort aims to foster consumer trust in the company. This research uses the prototyping method, an approach in the Software Development Life Cycle (SDLC) that focuses on developing working models. The creation of a website-based pet shop digital branding system can help shops introduce their businesses and products to buyers because it can be accessed directly from anywhere. Thus, buyers no longer need to visit the store in person to obtain information.